Comparison of artesunate and quinine in the treatment of severe Plasmodium falciparum malaria at Kassala hospital, Sudan - Abdallah, Tajeldin M; Elmardi, Khalid A; Elhassan, Asama H; Omer, Mona B; Elhag, Mousab S; Desogi, Mohamed A; Siddig, Mohammed F; Adam, Ishag (The Journal of Infection in Developing Countries, 2014)
Introduction: There is a need to investigate the treatment (artesunate and quinine) of severe malaria, as this will influence the outcome of morbidity and the mortality of the disease. Methodology: An open randomized trial conducted at Kassala, Sudan. Patients with severe P. falciparum malaria were randomly assigned to either intravenous artesunate at 2.4 mg/kg at 0, 12, and 24 hours, then daily, or intravenous quinine at a 20 mg/kg loading dose, then 10 mg/kg three times a day. Fever and parasite clearance and coma resolution time were compared between the two groups . Results: The two groups (47 in each group) were well matched in the clinical and biochemical characteristics. Hypotension, convulsions, severe anemia, hypoglycemia, cerebral malaria, and jaundice were the predominant manifestations of severe malaria. The mean (SD) of the fever clearance (10.8 [5.5] vs. 14.0 [8.1] hours, p = 0.028) and the parasite clearance time (16.5 [6.4] vs. 21.7 [11.3] hours, p = 0.007) were significantly shorter in the artesunate-treated patients. In comatose patients, there was no difference between the two groups in coma resolution time. Following quinine infusion, ten patients developed tinnitus (p < 0.001), and four had hypoglycemia (p = 0.033). Tinnitus and hypoglycemia were not detected in the artesunate group. One patient in the artesunate group died. Conclusions: Artesunate is more effective than quinine, in term of parasite and fever clearance time, in the treatment of P. falciparum malaria in eastern Sudan. The study found no difference between artesunate and quinine in coma resolution time.